Benefits of Information Resources Sharing in Nigerian Universities Libraries in Digital Age: Prospects and Hindrances - Odiri, Daniel Loretta; Ayinde, Ibrahim Munir (POMLIF Journal of Library and Information Science, 2019)
The information resolution has made libraries around the globe to adopt new philosophies and technologies for service delivery, provision of relevant, current and adequate information and also reduce the cost of information. University libraries have realized that no matter how they are sufficiently funded, it is difficult acquire all materials needed by their clientele. This articles examines the prospects and hindrances of information resources sharing in university libraries. It discusses the concept of information resources sharing, resources sharing in the digital age, rationale for resources sharing, benefits and challenges of resource sharing. It drew its conclusion and recommendations based on the numerous literature reviewed which include funding and maintenance of library resources, organizing staff training on the benefits of resource sharing and how it could be done in the digital age, there is need for constant power supply, provision of ICT resources to enable sharing of information and creating an environment that enables resource sharing to thrive.